Challenges of identifying children with Cystic Fibrosis to explore inequalities in social and health outcomes, using multiply linked data sources. (2018) - Griffiths, Rowena; Akbari, Ashley; Schlueter, Daniela; Taylor-Robinson, David; Tucker, David
No abstract available